Identification and localization of the structural proteins of anguillid herpesvirus 1 - van Beurden, Steven J (BioMed Central, 2011)
Many of the known fish herpesviruses have important aquaculture species as their natural host, and may cause serious disease and mortality. Anguillid herpesvirus 1 (AngHV-1) causes a hemorrhagic disease in European eel, Anguilla anguilla. Despite their importance, fundamental molecular knowledge on fish herpesviruses is still limited. In this study we describe the identification and localization of the structural proteins of AngHV-1. Purified virions were fractionated into a capsid-tegument and an envelope fraction, and premature capsids were isolated from infected cells. Proteins were extracted by different methods and identified by mass spectrometry. A total of 40 structural proteins were identified, of which 7 could be assigned to the capsid, 11 to the envelope, and 22 to the tegument. The identification and localization of these proteins allowed functional predictions. Our findings include the identification of the putative capsid triplex protein 1, the predominant tegument protein, and the major antigenic envelope proteins. Eighteen of the 40 AngHV-1 structural proteins had sequence homologues in related Cyprinid herpesvirus 3 (CyHV-3). Conservation of fish herpesvirus structural genes seemed to be high for the capsid proteins, limited for the tegument proteins, and low for the envelope proteins. The identification and localization of the structural proteins of AngHV-1 in this study adds to the fundamental knowledge of members of the Alloherpesviridae family, especially of the Cyprinivirus genus.